Metabolic counterparts of sodium accumulation in multiple sclerosis: A whole brain 23Na-MRI and fast 1H-MRSI study. (January 2019) - Donadieu, Maxime; Le Fur, Yann; Maarouf, Adil; Gherib, Soraya; Ridley, Ben; Pini, Lauriane; Rapacchi, Stanislas; Confort-Gouny, Sylviane; Guye, Maxime; Schad, Lothar R; Maudsley, Andrew A; Pelletier, Jean; et al.
Background: Increase of brain total sodium concentrations (TSC) is present in multiple sclerosis (MS), but its pathological involvement has not been assessed yet. Objective: To determine in vivo the metabolic counterpart of brain sodium accumulation. Materials/methods: Whole brain 23 Na-MR imaging and 3D- 1 H-EPSI data were collected in 21 relapsing-remitting multiple sclerosis (RRMS) patients and 20 volunteers. Metabolites and sodium levels were extracted from several regions of grey matter (GM), normal-appearing white matter (NAWM) and white matter (WM) T2 lesions. Metabolic and ionic levels expressed as Z -scores have been averaged over the different compartments and used to explain sodium accumulations through stepwise regression models. Results: MS patients showed significant 23 Na accumulations with lower choline and glutamate–glutamine (Glx) levels in GM; 23 Na accumulations with lower N -acetyl aspartate (NAA), Glx levels and higher Myo-Inositol (m-Ins) in NAWM; and higher 23 Na, m-Ins levels with lower NAA in WM T2 lesions. Regression models showed associations of TSC increase with reduced NAA in GM, NAWM and T2 lesions, as well as higher total-creatine, and smaller decrease of m-Ins in T2 lesions. GM Glx levels were associated with clinical scores. Conclusion: Increase of TSC in RRMS is mainly related to neuronal mitochondrial dysfunction while dysfunction of neuro-glial interactions within GM is linked to clinical scores.